Research and Trends of Socio-Scientific Issues in Natural Science Education: Bibliometric and Content Analysis Based on Systematic Literature Review - Thoriqi Firdaus (Journal of Progressive Science Education, 2025)
The implementation of Socio-Scientific Issues (SSI)-based learning has been widely carried out in developed countries that have received international attention in the field of science education. This study uses a mixed-method approach. The quantitative approach employs bibliometric analysis data, while the qualitative approach uses content analysis data based on a systematic literature review. The design used is a triangulation design with a one-phase model. The research data source uses the Scopus database from 2004–2023 with the search keywords “Socio-Scientific and Issue” and “Science Education.” The bibliometric data collection technique consists of three stages, namely defining the objective, selecting the sample, and statistical analysis. Meanwhile, the content analysis data collection technique uses the PRISMA model. The bibliometric results obtained 208 articles and were analyzed based on published SSI in Natural Science Education documents and authors, contribution of countries and affiliations, documents by subject area and co-occurrence network of the keywords, source articles of SSI, and citations. The content analysis results obtained 17 article studies included in the review with analysis based on study objective, methodology, main finding, and summary of discussion. Based on the results, it shows that the trend of SSI research from 2004–2023 has significantly increased with the highest research contribution from the United States. The most frequently studied influence of SSI in science education is scientific literacy skills, argumentation, reasoning, and problem-solving. The most frequently studied SSI topics are global warming and climate change. SSI-based learning strongly supports the implementation in science education, but teachers will face challenges in handling SSI because controversial issues will make it difficult to integrate with science content.